Notas breves sobre la Sentencia del TJUE (Sala Cuarta) de 20 mayo 2010 (Bilas: asunto C-111/09): la sumisión tácita en los litigios internacionales de seguro, consumo y trabajo - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
The ECJ Judgement Michal Bilas (C-111/09) of May 20, 2010, arises the question of the submission as an operative ground of jurisdiction in the context of Council regulation 44/2001 with regard to litigations relative to individual employment contracts, consumer contracts, and insurance contracts. The EJC chooses the affirmative answer. The present paper tries to demonstrate that the above mentioned solution not only is irreproachable from a legal point of view, but, and this is even more important, is the most efficient possible solution.